Mentoring programs support the integration of refugees - Magdalena Krieger; Philipp Jaschke; Martin Kroh; Nicolas Legewie; Lea-Maria Löbel (DIW Weekly Report, 2020)
Over a million people sought asylum in Germany between 2014 and 2016. During this time, many Germans began volunteering in various ways to help refugees and mentorship pro- grams in particular gained significance. As this report shows, participating in a mentorship program has a positive impact on refugees: They improve their language skills and become more socially active. Mentors experience the relationship positively and want to continue their volunteer work with refugees. The results presented in this report emphasize the importance of interaction between refugees and Germans. In the future, access to mentorship programs should be facilitated for additional groups, such as refugee women and refugees in rural areas.
Keywords: F22; J15; J18; 330; refugees; mentoring; integration; volunteering